Analysis of hydrochemical parameters and dissolved zinc interaction by using PHREEQC simulation. Issue 1 (1st December 2022) - Alimuddin, H; Andarani, P; Yokota, K; Inoue, T; Nguyen, M N
Abstract: Zinc is frequently reacting with inorganic species in water to form zinc species. Thus, the chemical speciation of Zinc in the aquatic environment has become a significant concern nowadays due to its adverse effect on humans and its potential toxicity in the water system. In this study, to investigate the interaction between dissolved zinc and hydro-chemical factors and to estimate the Zn speciation form, samples of river water were collected spatially from the Umeda River mainstream and tributaries in different seasons for one year. The hydrochemistry and dissolved zinc pollution characteristics of the samples were analyzed. Zn speciation was assessed by PHREEQC simulation. The result show that the main form of Zn speciation was Zinc free ion (Zn 2+ ) in all seasons. However, in summer and spring season, the ZnCO3 and ZnOH + concentration was higher than the other season. These speciation form may be attributed to the activities around the river in different season according to the similarities in downstream and upstream areas by the hierarchical cluster analysis result.